INNOVATIVE POTENTIAL OF AGRICULTURAL AND FOOD INDUSTRY: NATURE, IMPORTANCE, DEVELOPMENT CHALLENGES - Котвицька, Наталія Миколаївна (Journal of Strategic Economic Research, 2023)
The innovative potential of the agro-food sector is a key element in the development of agriculture and the food industry. It determines the industry's opportunities for implementing new technologies, production processes, and products that can increase production efficiency and competitiveness in the market. The essence of the innovative potential lies in the industry's ability to undergo innovative transformations, innovations, and effective use of available resources. The innovative potential includes technical, organizational, economic, personnel, and other opportunities that can be used to create and produce new products, solve problems, and improve production quality. The significance of the innovative potential for the agro-food sector is that it allows the industry to maintain its place in the market and ensure growth in production, product quality, and competitiveness at the international level. The innovative potential helps to implement new technologies that reduce production costs, increase crop yields and product quality, reduce environmental impact, and ensure food safety. The challenges of developing the innovative potential of the agro-food sector are related to the complexity of technological processes and insufficient funding for research and implementation of cutting-edge technologies. The article explores the concept of innovation potential in the agro-food sector. It discusses different interpretations and approaches to defining the concept of «innovation potential» and substantiates its essence. The article analyzes the impact of innovation potential on the development of the agro-food sector, highlights the importance of innovation processes in this industry, and investigates the problems hindering its development. The article proposes a model for coordinating innovation processes in the Ukrainian agro-food sector, taking into account available resources and opportunities. In particular, it discusses the possibilities of using innovative technologies, introducing the latest management methods, and attracting funding to develop innovative activities in the agro-food industry. The article also examines factors that stimulate innovation in the agro-food sector, such as scientific and technical potential, market conditions, industry competition, management efficiency, and more. Additionally, the article addresses the issue of developing infrastructure and creating innovation clusters to facilitate collaboration between businesses and research institutions in the agro-food sector. A model for coordinating innovation processes in the Ukrainian agro-food sector is proposed, and a number of factors that stimulate innovation activity in this industry are identified.